Fire Safety Design in Building - Maksum Tanubrata (Jurnal Teknik Sipil, 2007)
The main themes for fire safety planning may be described as follows ; Prevention of outbreak and growth of fire , Fire protection of Building structures, smoke control and escape planning. Fire load in a building can be roughly classified into 3 groups: (a). buildings materials, (b). furniture, and (c). daily goods. Building materials including linings, interior material of walls, ceilings, floors, partition walls, etc, and daily goods such as books, clothes, and so on.